In situ data analytics and indexing of protein trajectories. Issue 16 (17th January 2017) - Johnston, Travis; Zhang, Boyu; Liwo, Adam; Crivelli, Silvia; Taufer, Michela
Abstract : The transition toward exascale computing will be accompanied by a performance dichotomy. Computational peak performance will rapidly increase; I/O performance will either grow slowly or be completely stagnant. Essentially, the rate at which data are generated will grow much faster than the rate at which data can be read from and written to the disk. MD simulations will soon face the I/O problem of efficiently writing to and reading from disk on the next generation of supercomputers. This article targets MD simulations at the exascale and proposes a novel technique for in situ data analysis and indexing of MD trajectories. Our technique maps individual trajectories' substructures (i.e., α ‐helices, β ‐strands) to metadata frame by frame. The metadata captures the conformational properties of the substructures. The ensemble of metadata can be used for automatic, strategic analysis within a trajectory or across trajectories, without manually identify those portions of trajectories in which critical changes take place. We demonstrate our technique's effectiveness by applying it to 26.3k helices and 31.2k strands from 9917 PDB proteins and by providing three empirical case studies. © 2017 Wiley Periodicals, Inc. Abstract : As computing moves toward exascale, I/O bandwidth limitations and power concerns will require a fundamental change in the way data is analyzed and stored. We present a novel method of analyzing and indexing protein trajectory data in situ . The analysis computes metadata for conformations as they are generated during a simulation. The indexed trajectory can then be quickly examined and in depth analysis can be performed on the most relevant segments of a trajectory.